Vector-Valued Inequalities in the Morrey Type Spaces - Hua Wang (International Journal of Mathematics and Mathematical Sciences)
We will obtain the strong type and weak type estimates for vector-valued analogues of classical Hardy-Littlewood maximal function, weighted maximal function, and singular integral operators in the weighted Morrey spaces Lp,κ(w) when 1≤p<∞ and 0<κ<1, and in the generalized Morrey spaces Lp,Φ for 1≤p<∞, where Φ is a growth function on (0,∞) satisfying the doubling condition.